Draft Annual Plan 1994-95 Andhra Pradesh Volume-II (Sectoral Programmes) 8. Social Services - Planning Commission (Planning Commission, 1994)
Under this sector an outlay of Rs.2759.40 lakhs was provided in the Budget 1993-94 and the same outlay has been proposed for the draft annual plan also.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh